Stabilizing effects of group formation by Serengeti herbivores on predator-prey dynamics - Fryxell, John M.; Mduma, Simon; Masoy, Joseph; Sinclair, Anthony R. E.; Hopcraft, Grant J. C.; Packer, Craig (Frontiers in Ecology and Evolution, 2022)
Predator-prey theory often assumes that potential prey individuals are solitary and evenly distributed in space. This assumption is violated in social, mobile prey, such as many ungulates. Here we use data from 80 monthly field censuses to estimate the parameters for a power relationship between herd density and population density for 8 species of large herbivores commonly found in the diet of Serengeti lions, confirming a power relationship proposed from a preliminary Serengeti dataset (Fryxell et al. 2007). Here we extend our analysis of that model to demonstrate how parameters of the power function relate to average herd size and density-dependent changes in herd size and evaluate how interspecific variation in these parameters shapes the group-dependent functional response by Serengeti lions for 8 prey species. We apply the different prey-specific functional response models in a Rosenzweig-MacArthur framework to compare their impact on the stability of predator-prey dynamics. Model outcomes suggest that group formation plays a strong role in stabilizing lion-herbivore interactions in Serengeti by forcing lions to search over a larger area before each prey encounter. As a consequence of grouping by their prey, our model also suggests that Serengeti lions are forced to broaden their diets to include multiple species of prey in order to persist, potentially explaining the generalist foraging by lions routinely recorded across multiple ecosystems.